Online discussion on WhatsApp application as a knowledge sharing among students / Ahmad Norsyakir Hanis Abdul Malek [et al. ] - Abdul Malek, Ahmad Norsyakir Hanis; Mohd Hasim, Ahmad Nufairi; Baharuddin Shah, Muhammad Affandy; Ismail, Muhammad Amar Fakhri (2014)
The purposes of conducted this research is to identify the using of WhatsApp application as medium for a knowledge sharing among students and also to make a comparison in the practise of online discussion through WhatsApp application between two faculties in difference branches of UiTM. The existing or WhatsApp application in this era of technology has made students prefer to share knowledge through this medium because of the borderless worlds as an advantage to them. The methodology is adopted to measure the significance of the application that been used by students for knowledge sharing and also to discover others types of medium recently been used, The research relieved that the majority of students are used WhatsApp application for specific purposes in certain situation. It also could help the students in their academic matters.